Nanoparticles and plant Biotechnology - Mobasseri Moghadam, Mohammad; Motalleb, Gholamreza (Research in Biotechnology, 2015)
Among the advances in technology, nanotechnology has an important role. With increasing rate of population, traditional agriculture will not be accountable the population food needs. The use of plants to produce nanoparticles is a biological system, cost-effective and environmentally friendly. The aim from nanotechnology in agriculture and biotechnology is development new methods for rapid diagnosis of plant diseases and needs with the use of biosensors, improving agricultural products, reduce environmental pollution, reduce costs, producing new products and engineered according to the increasing population. This review article provides an overview of the nanoparticles production in plants and their applications in agriculture, biotechnology, improved crops, and hazards of nanoparticles.